Predictors of urinary retention in benign prostate hyperplasia - Mahakalkar, Chandrashekhar C.; Prasad, Ayushree; Kaple, Meghali N.; Jain, Niket N.; Khadatkar, Aniket R.; Jaipuriya, Parag K. (International Journal of Research in Medical Sciences, 2016)
Background: Acute urinary retention (AUR) is one of the most significant complications or long-term outcomes of benign prostatic hyperplasia (BPH). Because of the high prevalence of BPH and its effect on the patient’s quality of life, additional research is needed to better predict the risk factors of AUR. The study was aimed to find out the incidence and factors responsible for retention of urine in BPH. Methods: It was a prospective study, conducted at a medical college after the approval from IEC. The study included the patients admitted to the surgical wards admitted with the symptoms of lower urinary tract symptom and presented with acute urinary retention. Duration of the study was 2 months. A total 40 patients were studied over this duration. The outcome of the study was analyzed by these factors: Age in years, Symptom severity, Prostate Volume on DRE and USG Grade. Results: The mean age of presentation was 64.87±7.85 with median age of 65 years (range 45-82 years) with mean IPSS score of 17.45and the mean PVR was 110.80 ± 85.52 with median 110 (range 0-500). Maximum number of patients having Grade 3 and 4 enlargements had PSA level 9-12 ng/ml. The PSA levels and the grade of enlargement on USG were statistically significant (p-0.004). Conclusions: Out of the four factors considered to be the independent risk factors, all of them have positive correlation with the symptom of acute urinary retention. None of these four factors i.e. age in years, symptom severity, prostate Volume on DRE and USG grade could establish significant correlation.